The Causes Of Stunting And Preventive Stunting Action - Nugraha, Pratama Dharmika; Sugiharto , Sugiharto; Utomo, Andri Wahyu; Mandalawati, Titin Kuntum (Proceedings of International Conference on Science, Education, and Technology, 2023)
Health is one of the basic needs of people in order for them to do their obligations and enjoy life. One of the health problems that concern the goverment of Indonesia through the ministry of health is about how to reduce the prevalence of short children or stunting. The cause of the stunting condition ismultidimensional because it is not only caused by nutritional factor and bad experiences of pregnant women and children. An understanding of the cause of stunting needs to be explained to the community. The act of preventive stuntingis indispensable so as that aprecaution could be done to impact the condition of the children in Indonesia. Educating the community and suporting the government programs of the republic of Indonesia for the development of the country and prosperity of the people are a must.